Effect of impeller diameter on Nusselt number in mechanically agitated vessel. Issue 4 (19th August 2019) - Sk, Ansar Ali; Kumar, Pardeep; Kumar, Sandeep
Abstract : Purpose: The purpose of the study is to developed the effect of Nusselt number on impeller diameter in agitated vessel, which is beneficial to find out the heat transfer coefficient in the process industry. A comparison has been done between the experimental and calculated Nusselt numbers with standard deviation found to be 8.03 per cent. Design/methodology/approach: For studying the effect of impeller diameter on Nusselt Number, the heat transfer measurements were made with three different impellers of diameter. Although the diameter of impeller, Da shows its effect in Reynolds number, an attempt has been made to find the relationship between the impeller diameter and Nusselt number. A correlation between (NNuj /N ″ Pra 1/3 N ″ Rea 2/3 ) vs Da /DT and (NNuoc /N ″ Pra 1/3 N ″ Rea 2/3 ) vs Da /Dc in which data of three fluids [1, 2 and 4 per cent carboxy methyl cellulose solution of A type (CMC-A) solutions] have been plotted. Findings: The heat transfer data for agitated Newtonian and non-Newtonian fluids have been successfully correlated by using the viscosity of the fluid evaluated at the impeller tip assuming a cylinder of diameter equal to that of impeller rotating in an infinite fluid. Data of 1, 2 and 4 per cent CMC-A, for three impeller diameters, have been correlated by equations. Using the above concepts of Reynolds and Prandtl numbers, Nusselt Numbers and Da /DT, it is also possible to correlate the available published data for other non-Newtonian fluids obtained with different impeller geometries. Originality/value: A set up was made for studying the effect of impeller diameter, the heat transfer measurements were made with three impellers of diameter 7.5, 12.7 and 18.35 cm respectively. Although the diameter of impeller, Da shows its effect is Reynolds number, an attempt has been made to find the effect of Da /DT ratio on Nusselt number.